An Examination of Bullying Behaviors in Children in Relation to Problematic Media Use and Digital Game Addiction - Kevser Tozduman Yaralı; Sibel Şeker; Rabia Ceren Çavga (Hacettepe University Faculty of Health Sciences Journal, 2026)
Objectives: This study aimed to examine bullying behaviors in relation to problematic media use and digital game addiction among children. The research employed a quantitative analytic cross-sectional design.Materials and Methods: The study sample consisted of 184 children aged 5–6 years, 184 parents, and six preschool teachers. Data were collected using a Personal Information Form, the Problematic Media Use Scale for Children, the Bullying and Victimization Behavior Assessment Form, and the Digital Game Addiction Tendency Scale. Data were analyzed with SPSS version 25.0.Results: The results indicated that as the subscale of the Digital Game Addiction Scale for escapism increased, children’s tendency to be in the victim role and problematic media usage also increased. A significant relationship was found between children in the passive-bully role and the life-immersion subscale of the Digital Game Addiction Scale. A strong association was demonstrated between the subscales of life dissociation from life, conflict, constant play, and life reflection on the Digital Game Addiction Scale and the scores on the Problematic Media Use Scale. In addition, digital game addiction and problematic media use were found to have predictive effects on children’s bullying behaviors.Conclusion: Developing intervention programs addressing digital game addiction and problematic media use during the preschool period is anticipated to serve as a preventive measure to reduce bullying behaviors.